IMPELEMENTASI ALGORITMA LUC UNTUK PENGAMANAN PESAN BERBASIS ANDROID - Johan Basitu Rahman; Muhsin m; Yati Nurhayati (NUANSA INFORMATIKA, 2018)
One method for securing data or information is by using cryptography method. The LUC algorithm is a cryptographic method using two different words in its cryptosystem. To encrypt language uses files that has a public key, encrypted results are encrypted files that are safe from intruders. Furthermore, decrypting the processed file using decryption using the private key will return the same text file as the original one. The operation on the LUC algorithm is done in the number domain, therefore, before encryption is done, the text is first converted to numeric form.Keywords : Cryptography, LUC Algorithm, Encryption, Description